The impact of long-term care insurance on household expenditures of the elderly: Evidence from China. - Tianshu Zhang; Zeping Hu; Kaiyue Zhang; Xinran Li (PLoS ONE)
This study aims to investigate the impact of China's long-term care insurance (LTCI) pilot on household expenditures of the elderly. Utilizing the China Health and Retirement Longitudinal Study (CHARLS) 2015-2020 three-period longitudinal panel data, we examine the policy effects of LTCI using the Differences-in-Differences (DID) approach. The results indicate that the implementation of LTCI significantly reduces medical (p<0.05) and healthcare expenditures (p<0.05) for elderly households, while substantially increasing non-medical healthcare expenditures (p<0.01) and total expenditures (p<0.01). This effect is more pronounced for older households in rural areas or with lower levels of education. Furthermore, the improvement in household expenditures is strongly associated with the health status of the elderly and intergenerational economic support. These findings provide empirical evidence that LTCI enhances household expenditures and the quality of life for the elderly, which is crucial for the development of LTCI in China and other middle-income developing countries.